Conflicts between Farmers and Livestock Breeders in Mali: A Review of Dynamics and Issues in the Mopti Region - Ba, Baba (International Livestock Research Institute, 2023)
The central delta of the Niger is characterized by the coexistence of various production systems sharing water and land as common elements. These systems have long interacted, complementing and substituting one another through efficient socio-spatial organization. However, several factors have led to the emergence of challenges between users of natural resources, especially farmers and herders. This makes the central delta of the Niger one of the Sahelian regions where conflicts have taken alarming proportions. This literature review aims to highlight the issues characterizing conflicts between herders and farmers in Mali, particularly in the Mopti Region. After analysing studies on factors weakening the agropastoral context of the delta, we focus on climatic, environmental, socioeconomic, and politico-institutional aspects to identify the drivers and triggers of conflicts. We also examine the management and resolution modalities of these conflicts, as well as their impacts on food production systems. This study is part of the research activities supported by the CGIAR through the International Livestock Research Institute (ILRI). Our objective is to contribute to ongoing research on land and conflicts, especially within the framework of the Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) project, with case studies in Sudan and Nigeria, along with a contextual study in Mali. It is also part of the CGIAR’s Fragility, Conflict, and Migration initiative. In light of this review, it becomes apparent that conflicts between farmers and herders are fueled by various factors, such as climate change, evolving governance modes, and ongoing transformations in agricultural production systems within the delta. These conflicts destabilize social relations between communities, leading them into increasingly complex dynamics. Moreover, it is evident that agropastoral conflicts are strongly influenced by a fragile political and security context, linking them to the emergence of jihadist or self-defence armed groups.